RASIONALITAS PENGGUNAAN ANTIBIOTIK PADA PASIEN DIABETES MELITUS DENGAN ULKUS DIABETIKUM DI BANJARMASIN, KALIMANTAN SELATAN, INDONESIA - Annida Mujahidah Nurul Azmi; Yulistia Budianti Soemarie; Juwita Ramadhani (Sekolah Tinggi Ilmu Kesehatan Samarinda, 2025)
otential to cause serious complications. Antibiotic therapy is one of the treatment options for patients with diabetic ulcers. Overuse of antibiotics can lead to resistance, which can make therapy less successful. This study aims to determine the percentage of rational antibiotic use and its effect on therapy outcomes in diabetic ulcer patients. This study aims to identify the percentage of rational antibiotic use and its effect on therapeutic outcomes in diabetic ulcer patients in Banjarmasin Hospital. This study was an observational study with a cross-sectional method and data collection in this study was carried out retrospectively during the period July-December 2023. The rationality of antibiotic use was evaluated using the Gyssens method and the correlation of rationality with therapeutic outcomes was analyzed using the chi square test. The study subjects were 94 patients with diabetic ulcers who met the inclusion criteria. The rationality of antibiotic use with the Gyssens category was in category 0 (appropriate) for 65 patients (69%), category IIb (inappropriate interval) for 3 patients (3%), category IIIa (too short) for 10 patients (11%), category IIIb (too long) for 6 patients (6%), category IVa (more effective) for 3 patients (3%), and category IVc (cheaper alternative) for 7 patients (7%). The results of the Chi-Square Test state that there is a significant correlation between the rationality of antibiotic use and therapeutic outcomes in the form of a decrease in the degree of diabetic ulcers. 69% of patients received rational antibiotic therapy and 31% received irrational therapy based on the Gyssens method and there was a correlation between the rationality of antibiotic use and therapeutic outcomes in the form of a decrease in the degree of diabetic ulcers.